If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x(8 + 6x) = 20 (8 * 8x + 6x * 8x) = 20 (64x + 48x2) = 20 Solving 64x + 48x2 = 20 Solving for variable 'x'. Reorder the terms: -20 + 64x + 48x2 = 20 + -20 Combine like terms: 20 + -20 = 0 -20 + 64x + 48x2 = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-5 + 16x + 12x2) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-5 + 16x + 12x2)' equal to zero and attempt to solve: Simplifying -5 + 16x + 12x2 = 0 Solving -5 + 16x + 12x2 = 0 Begin completing the square. Divide all terms by 12 the coefficient of the squared term: Divide each side by '12'. -0.4166666667 + 1.333333333x + x2 = 0 Move the constant term to the right: Add '0.4166666667' to each side of the equation. -0.4166666667 + 1.333333333x + 0.4166666667 + x2 = 0 + 0.4166666667 Reorder the terms: -0.4166666667 + 0.4166666667 + 1.333333333x + x2 = 0 + 0.4166666667 Combine like terms: -0.4166666667 + 0.4166666667 = 0.0000000000 0.0000000000 + 1.333333333x + x2 = 0 + 0.4166666667 1.333333333x + x2 = 0 + 0.4166666667 Combine like terms: 0 + 0.4166666667 = 0.4166666667 1.333333333x + x2 = 0.4166666667 The x term is 1.333333333x. Take half its coefficient (0.6666666665). Square it (0.4444444442) and add it to both sides. Add '0.4444444442' to each side of the equation. 1.333333333x + 0.4444444442 + x2 = 0.4166666667 + 0.4444444442 Reorder the terms: 0.4444444442 + 1.333333333x + x2 = 0.4166666667 + 0.4444444442 Combine like terms: 0.4166666667 + 0.4444444442 = 0.8611111109 0.4444444442 + 1.333333333x + x2 = 0.8611111109 Factor a perfect square on the left side: (x + 0.6666666665)(x + 0.6666666665) = 0.8611111109 Calculate the square root of the right side: 0.927960727 Break this problem into two subproblems by setting (x + 0.6666666665) equal to 0.927960727 and -0.927960727.Subproblem 1
x + 0.6666666665 = 0.927960727 Simplifying x + 0.6666666665 = 0.927960727 Reorder the terms: 0.6666666665 + x = 0.927960727 Solving 0.6666666665 + x = 0.927960727 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + x = 0.927960727 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + x = 0.927960727 + -0.6666666665 x = 0.927960727 + -0.6666666665 Combine like terms: 0.927960727 + -0.6666666665 = 0.2612940605 x = 0.2612940605 Simplifying x = 0.2612940605Subproblem 2
x + 0.6666666665 = -0.927960727 Simplifying x + 0.6666666665 = -0.927960727 Reorder the terms: 0.6666666665 + x = -0.927960727 Solving 0.6666666665 + x = -0.927960727 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + x = -0.927960727 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + x = -0.927960727 + -0.6666666665 x = -0.927960727 + -0.6666666665 Combine like terms: -0.927960727 + -0.6666666665 = -1.5946273935 x = -1.5946273935 Simplifying x = -1.5946273935Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.2612940605, -1.5946273935}Solution
x = {0.2612940605, -1.5946273935}
| .25(12x)=.6+.35x | | -2(x-4)=-6(2+x) | | 5(x+1)+51=-2x | | 4x+14=6x-26 | | 2m+7(m-1)=-21-5m | | 5+6y=5y+10 | | -abx^2+bcx+1=0 | | 5+y^2+7=3 | | 15w-22=-111 | | 8v+4=2v-8 | | 4(x-4)+2x=4x-6 | | (6y+5)(y-2)= | | 13x+7=6x+14 | | -3+7q=-7+9q | | -(1+6m)+6m=-11+3(r-7) | | Y=(5t^2)*(5t^3) | | -2(3)(-5)= | | 3(7-4x)=-39 | | 12=96 | | 3x+3+55=180 | | 4(5x-7)=52 | | 4x^3-34x^2+70x-25=0 | | -5s-9=-2s | | 2x^2-12x=32x-192 | | 3(-7+7x)=168 | | 5(8-8x^2)=8 | | 6y-28=4y-12 | | -7u=-8u+6 | | f(x)=ln(x+1) | | 12x+36=-3x-81 | | -6-5x=4x-51 | | -5+2x-8x+4x=40 |